Environment, space, and morphological variation of projectile points in Patagonia (Southern South America) - Cardillo, Marcelo (2016)
The aim of this work is to assess shape variation in Patagonian stemmed projectile points related to spatial and environmental factors by means of geometric morphometric and multivariate methods. The sample includes 1445 projectile points from Fuego-Patagonia (Southern South America) assigned to Late Holocene (ca. 3600 BP). Besides the authors' own research and the revision of published literature, most of the projectile points come from a broad survey program of museum collections. Previous research showed a trend of shape change related to latitudinal axis in continental Patagonia, but no digital sample was available at that time from some areas, especially Isla Grande de Tierra del Fuego, in southernmost Patagonia. With the purpose of extending our analysis to overall Patagonia (continental and insular) and taking advantage of the new digital dataset available, we focus on the correlation between spatial and environmental variables (precipitation and temperature) and morphological change. The new results obtained show a pattern of high morphological variation in lithic projectile points across Patagonia. In particular, we note that there is not a clear global trend for the distribution of shapes along the study area in relation to environment at the large scale considered in the present study. However, smaller scale spatial patterns were detected which allow discussing the role of local variations in environment, resource availability, technological strategies, reduction intensity and/or mobility ranges in overall technological behavior.